2019
DOI: 10.3389/fmicb.2019.02550
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Metabolomics Analyses of Clavulanic Acid-Producing Streptomyces Species Provides Insight Into Specialized Metabolism

Abstract: Clavulanic acid is a bacterial specialized metabolite, which inhibits certain serine β-lactamases, enzymes that inactivate β-lactam antibiotics to confer resistance. Due to this activity, clavulanic acid is widely used in combination with penicillin and cephalosporin (β-lactam) antibiotics to treat infections caused by β-lactamase-producing bacteria. Clavulanic acid is industrially produced by fermenting Streptomyces clavuligerus, as large-scale chemical synthesis is not commercially feasible. Other than S. cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 112 publications
2
38
0
Order By: Relevance
“…However, we did not observe a similar trend in all species analyzed as in some cases the number of predicted VOC BGCs did not correlate with those actually detected. For instance, S. clavuligerus , which is known to produce a wide range of specialized metabolites, including β-lactam antibiotics and molecules of plant origin [ 114 ], contains many predicted BGCs ( Supplemental Table S3 ) and produced five identifiable VOCs ( Figure 2 B, Supplemental Table S5 ). However, terpenes were not detected in S. clavuligerus headspace samples in our study ( Figure 2 B, Supplemental Table S5 ), even though the species possesses 12 predicted BGCs for such metabolites ( Figure 1 B, Supplemental Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we did not observe a similar trend in all species analyzed as in some cases the number of predicted VOC BGCs did not correlate with those actually detected. For instance, S. clavuligerus , which is known to produce a wide range of specialized metabolites, including β-lactam antibiotics and molecules of plant origin [ 114 ], contains many predicted BGCs ( Supplemental Table S3 ) and produced five identifiable VOCs ( Figure 2 B, Supplemental Table S5 ). However, terpenes were not detected in S. clavuligerus headspace samples in our study ( Figure 2 B, Supplemental Table S5 ), even though the species possesses 12 predicted BGCs for such metabolites ( Figure 1 B, Supplemental Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, terpenes were not detected in S. clavuligerus headspace samples in our study ( Figure 2 B, Supplemental Table S5 ), even though the species possesses 12 predicted BGCs for such metabolites ( Figure 1 B, Supplemental Table S3 ). Previous reports have shown that the plant-associated terpenoids carveol, cuminyl alcohol and hydroxyvalerenic acid were detected during liquid chromatography–MS/MS analysis of certain S. clavuligerus cultures extracted with methanol/ethyl acetate [ 114 ]. In a separate report, terpenes were not detected in n -hexane extracts of S. clavuligerus cultures grown on SFM or YMS media (also used in the current study) when subjected to GC-MS analysis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptomyces clavuligerus is the industrial producer of clavulanic acid, a β-lactamase inhibitor used in combination with β-lactam antibiotics to treat certain otherwise-resistant bacterial infections [ 3 ]. In addition, S. clavuligerus is also known to produce cephamycin C [ 4 ], 5 S clavams [ 5 ], naringenin [ 6 , 7 ], holomycin [ 8 ], and tunicamycins [ 8 ]. Different genome sequencing studies have reported the presence of 49–58 SM BGCs in S. clavuligerus [ 9 , 10 ], most of which are thought to be cryptic (or silent) as the identities of their SM products remain unknown [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of production or improved yields of these cryptic SMs can lead to the identification of new biosynthetic capabilities. For example, S. clavuligerus was recently shown to produce certain plant-associated metabolites [ 6 , 7 ], previously not thought to be synthesized by bacteria [ 6 ]. In addition, genes for the biosynthesis of some of these metabolites do not reside in defined BGCs, providing additional challenges for their identification and heterologous expression.…”
Section: Introductionmentioning
confidence: 99%